The relationship between nuclear factor-erythrocyte-related factor 2 and antioxidant enzymes in the placenta of patients with gestational diabetes and the metabolism of umbilical cord endothelial cells: Nuclear factor-erythrocyte-related factor 2 - Yin, Xiaoxiao; Nie, Juan; Nie, Xiaoqian; Nie, Yumei (Cellular and Molecular Biology, 2022)
The paper aimed to explore the relationship between nuclear factor erythroid 2 related factor 2 (Nrf2), antioxidant enzymes and the metabolism of umbilical cord endothelial cells in the placenta of patients with gestational diabetes (GDM). A total of 200 pregnant women who underwent an obstetric examination at the Municipal Maternity and Child Health Hospital from March 2018 to December 2019 were selected, with an average age of 30.91±3.24. According to the plasma glucose level and oral glucose tolerance test (OGTT), pregnant women were divided into a control group and an observation group. Blood samples were collected from these pregnant women, serum was removed, put into a centrifuge tube and stored in the refrigerator of the laboratory at - 80 °C. Placental tissue was collected for biochemical analysis. GSH level was detected by absorbance kit, and serum MDA content was detected by spectrophotometry. The expression levels of Heme oxygenase-1(HO-1), Nrf2, and NQO1 protein in placental tissue were analyzed by gel electrophoresis. Western blot analysis was used to detect the protein expression levels of Bach1 and Keap1 in endothelial cells. PCR real-time analysis was used to detect the expression of GSH and NQO1 mRNA. Results showed that the SOD and GSH levels in the serum of the observation group were lower than those of the control group (P<0.05). The protein expression levels of HO-1, Nrf2 and NQO1 in the observation group were higher than those in the control group (P<0.05). The GSH level of the HNE+ observation group was lower than that of the HNE+ control group before stimulation (P<0.05). 1.5 hours after the stimulation, the GSH levels of the two groups of cells were decreased. After 6 hours, the GSH levels of the two groups began to increase. The GSH level of HUVEC in the HNE+ observation group was lower than that of the HNE+ control group after 48 hours. The expression level of Bach1 protein in the HNE+ observation group was lower than that in the HNE+ control group (P<0.05). The expression level of Keap1 protein in the HNE+ observation group and HNE+ control group did not change (P>0.05). The expression levels of GSH and NQO1 mRNA in the HNE+Nrf2 silence group were lower than that in the Nrf2 silence group (P<0.05). The expression levels of GSH and NQO1 mRNA in the HNE+Nrf2 overexpression observation group were higher than those of the HNE+Nrf2 silence group (P<0.05). The apoptosis of trophoblast in the placenta of GDM patients was significantly decreased. The continuous lack of redox signals in fetal endothelial cells in patients with gestational diabetes can destroy the defense ability of cells in the uterus against oxidative stress. Nrf2 antioxidant defense pathway can provide therapeutic targets for reducing oxidative stress associated with diabetes and aging.